Preparation of Nano to Submicro‐Porous TiMo Foams by Spark Plasma Sintering1 . Issue 2 (29th November 2016) - Zhang, Faming; Wang, Lili; Li, Ping; Liu, Suli; Zhao, Peipei; Dai, Ge; He, Siyuan
Abstract : The nano to submicro‐porous β‐titanium molybdenum (TiMo) foams are prepared by dealloying of (TiMo)1–x Cux master alloys using a solid state dealloying method. The dealloying is performed within Mg powders by a pressureless spark plasma sintering (SPS). Experimental results show that Cu atoms in the master alloy are selectively dissolved into Mg powders during heating, the Ti and Mo atoms are spontaneously organized into homogeneous open‐cell β‐TiMo foams. The foams from (Ti15Mo)40 Cu60 alloy have BET surface area of 28.96 m 2  g –1 and pore sizes mostly in the range of 3.42 to 50 nm. The hardness and elastic modulus of the foams decrease dramatically with nanoporosities from 55.1 to 74.2%. Solid state dealloying by using pressureless SPS is promising for developing functional nanoporous (NP) Ti alloy foams. Abstract : Nano to submicro‐porous β‐TiMo foams are prepared by dealloying of TiMoCu master alloy using a solid state dealloying method within Mg powders, which are conducted by a pressureless spark plasma sintering. Solid state dealloying in powders is promising for developing NP Ti alloy foams.